Sensitivity of option contracts - Martinkute-Kauliene, Raimonda (Business: Theory and Practice, 2013)
There are plenty of reasons why investors use option contracts in their portfolios. The main reason for using such contracts or their strategies is to hedge against risk concerned with the uncertainty of underlying asset price movements. The identification of risk factors and their management is essential for all kinds of business. However, the process of risk assessment and management is especially important in the case of using complex activities such as option contracts. Options have characteristics that may make them less attractive for some investors. Options can be risky but provide opportunities to profit for those who properly use this flexible instrument. Before the investor can explore the application of strategies for various options, first, he must be able to analyze and understand the degree of risk they impose. The purpose of the article is to analyze the basic measures of option risk, sensitivity factors and their meaning to the investor. When understanding, calculating and using such measures as delta, gamma, theta and vega, the investor can manage the riskiness of the option and the whole portfolio. Each Greek letter measures a different dimension of risk in an option position.